Soil application of effective microorganisms and nitrogen alleviates salt stress in hot pepper (Capsicum annum L.) plants - Abdelkhalik, Abdelsattar; Abd El-Mageed, Taia A.; Mohamed, Ibrahim A. A.; Semida, Wael M.; Al-Elwany, Omar A. A. I.; Ibrahim, Ibrahim M.; Hemida, Khaulood A.; El-Saadony, Mohamed T.; AbuQamar, Synan F.; El-Tarabily, Khaled A.; Gyushi, Mohammed A. H. (Frontiers in Plant Science, 2023)
The application of effective microorganisms (EMs) and/or nitrogen (N) have a stimulating effect on plants against abiotic stress conditions. The aim of the present study was to determine the impact of the co-application of EMs and N on growth, physio-biochemical attributes, anatomical structures, nutrients acquisition, capsaicin, protein, and osmoprotectant contents, as well as the antioxidative defense system of hot pepper (Capsicum annum L.) plants. In the field trials, EMs were not applied (EMs-) or applied (EMs+) along with three N rates of 120, 150, and 180 kg unit N ha-1 (designated as N120, N150, and N180, respectively) to hot pepper plants grown in saline soils (9.6 dS m-1). The application of EMs and/or high N levels attenuated the salt-induced damages to hot pepper growth and yield. The application of EMs+ with either N150 or N180 increased the number, average weight and yield of fruits by 14.4 or 17.0%, 20.8 or 20.8% and 28.4 or 27.5%, respectively, compared to hot pepper plants treated with the recommended dose (EMs- × N150). When EMs+ was individually applied or combined with either N150 or N180, increased accumulation of capsaicin were observed by 16.7 or 20.8%, protein by 12.5 or 16.7%, proline by 19.0 or 14.3%, and total soluble sugars by 3.7 or 7.4%, respectively, in comparison with those treated with the integrative EMs- × N150. In addition, the non-enzymatic contents (ascorbate, and glutathione) and enzymatic activities (catalase, superoxide dismutase, and glutathione reductase) of the antioxidant defense systems significantly increased in hot pepper plants treated with EMs+ alone or combined with N150 or N180 under salt stress conditions. Higher accumulation of nutrients (N, P, K+, and Ca2+) along with reduced Na+ acquisition was also evidenced in response to EMs+ or/and high N levels. Most anatomical features of stems and leaves recovered in hot pepper plants grown in saline soils and supplied with EMs+ and N. The application of EMs and N is undoubtedly opening new sustainable approaches toward enhancing abiotic stress tolerance in crops (e.g. hot pepper).